Dengeki Daisy. Vol. 16 - Motomi, Kyousuke (Shojo beat manga., 2015)
"A huge explosion goes off on the uninhabited island that Kurisaki, Teru and Akira are on! What is the fate of these three, and what does their future hold? The Dengeki Daisy series comes to a conclusion, followed by bonus material, two special chapters, and the author's debut manga, 'No-Good Cupid'!"--Back cover.